Pengembangan Openchart untuk Optimalisasi Pemasaran Produk Cemilan dan Kerajinan pada UMKM Kecamatan Kinali - Putri, Aimala; Annas, Firdaus; Amanda Putri, Diva (JOVISHE : Journal of Visionary Sharia Economy, 2024)
Development of Openchart aims to overcome the problem of limited promotion faced by micro, small and medium enterprises (MSMEs) in Kinali sub-district. by micro, small, and medium enterprises (MSMEs) in Kinali sub-district. Despite having high quality products, many MSMEs in this area struggle to reach a wider market due to ineffective marketing strategies. market due to ineffective marketing strategies and the lack of utilization of information technology. and the lack of utilization of information technology. Through the Openchart approach, approach, this research focuses on the development of a visual platform that can present product data in an attractive and informative way. This aims to make it easier for consumers to understand the advantages and variety of products offered. By utilizing Openchart, MSMEs can visualize information about their snack and craft products, including prices, raw materials, and manufacturing processes, which is expected to increase the attractiveness of their products. raw materials, and the manufacturing process, which is expected to increase the attractiveness of the products in the eyes of consumers. products in the eyes of consumers. In addition, this research also identified challenges faced by MSMEs in marketing their products, such as limited budget for promotion, lack of knowledge about digital marketing, and increasingly fierce competition. By optimizing marketing through Openchart, it is expected that MSMEs in Kinali sub-district can increase the visibility of their products, expand the market's promotional goose, and ultimately boost local economic growth. encourage local economic growth. This research will also involve training for MSME players so that they can utilize technology better. technology better. It is hoped that, with the right support, MSMEs in Kinali sub-district will not only be able to compete in the local market but also reach out to the local market. will not only be able to compete in the local market but also reach a wider market, including online markets. including online markets. With this step, it is expected that MSMEs can be more competitive and sustainable, and have a positive impact on the local economy. for the local economy. Local governments are also expected to provide greater support for the development of MSMEs in the Kec. Kinali.